Intestinal Short-Chain Fatty Acids in Patients with Bronchial Asthma - O. Yu. Zolnikova; N. D. Potskhverashvili; N. I. Kokina; A. S. Trukhmanov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. Tostudy the content and profile of short-chain fatty acids (SCFAs) in faeces of patients with bronchial asthma and healthy individuals, as well as to evaluate possible correlations between the SCFA spectrum and clinical phenotype of patients with bronchial asthma. Materials and methods. 44 patients with asthma and 17 healthy volunteers participated in the study. All participants underwent a generally accepted range of clinical and laboratory studies, as well as functional respiratory tests. The SCFA spectrum was determined using gas-liquid chromatographic analysis. The results of patients with asthma showed a significant decrease in the total fatty acid content in faeces (p <0.001); changes in the absolute concentrations of individual acids, such as acetate (p <0.001), propionate (p <0.001) and butyrate (p <0.001); as well as a change in the total isoacid content (p <0.001). In 83% of the cases, the anaerobic type of the SCFA spectrum was detected. The aerobic type of the SCFA metabolic profile was detected in 17% of the cases. The change in the metabolic profile did not depend on the phenotype of the disease.Conclusion. Changes in SCFAs indicate pronounced disorders in the microbiocenosis of the intestinal biotope. The values of the anaerobic index in the context of various changes in the acid metabolic profile indicate the disturbance of the microorganism’s habitat, contributing to the growth of anaerobic or aerobic microflora populations.